Calidad de vida, funcionalidad familiar y adherencia al tratamiento en el paciente en hemodialisis ambulatoria, Pasaje 2016. - Goya Rodríguez, Ginger Tamara (2017)
The main objective of the study is to statistically compare the relationship between the quality of life and family functionality of people with chronic terminal renal disease on hemodialysis with adherence to treatment in the Canton Pasaje of the El Oro Province. Method: An analytical study established the relationship between quality of life and family functionality with the therapeutic adherence of people who are in renal replacement therapy (hemodialysis) living in the Canton Pasaje of El Oro, during the period from January to September of 2016. The Morisky Green, KDQOL-TM36 and FFSIL tests were applied to obtain the dependent variable and independent in their order, which were initially validated by means of a pilot test. The SPSS statistical package was used to obtain results and cross-check variables. Results: Participants had a mean age of 59 years ± 14 -DT-years, 54.2% were men, 66.7% came from the Urban area, 50% were married, 43.8% were baccalaureate Incomplete, only 10.4% had less than one year of dialysis and 81.3% had both diabetes mellitus and hypertension and pre-existing comorbidities. There was a significant relationship between quality of life and therapeutic adherence (Chi2 calculated: 30.08; p <0.05; V Cramer: 0.79), as well as between family functionality and therapeutic adherence (Chi2 calculated: 33.56, p <0.05, V Cramer: 0.8) Keywords: Family, chronic illness, adherence, quality of life, hemodialysis.